Humanizing the frontlines: individuating connections reduce customer mistreatment - Trinh, Elizabeth N.; Lee Cunningham, Julia (Organizational Behavior and Human Decision Processes, 2026)
Customer mistreatment of frontline service workers persists, even as technological advancements have reshaped how services are delivered. In many service encounters, employees are perceived primarily through their functional role, as instruments of service rather than as people. This paper draws on theories of workplace objectification and customer–employee service interactions to introduce the concept of individuating connections: brief relational moves in service encounters that surface person-revealing cues about the employee, shifting customer's perception from a role-occupant to individual. We propose that individuating connections increase customers' humanization of employees, which in turn reduces mistreatment. Four main studies—a field experiment in a U.S. supermarket chain (Study 1), an in-person dyadic laboratory experiment involving a car sale (Study 2), an online dyadic conversation experiment simulating a hotel exchange (Study 3), and an online dyadic conversation experiment about a restaurant service exchange (Study 4)—as well as two supplemental studies offer convergent evidence supporting this effect. We reveal that small, scalable relational interventions leveraging individuating connections can counteract the objectifying dynamics common in service contexts and meaningfully alter how customers treat the people serving them.